Functional diversity and redundancy of tropical forest mammals over time. (6th September 2020) - Gorczynski, Daniel; Beaudrot, Lydia
Abstract: Globally, tropical rain forests comprise some of the most diverse and functionally rich ecosystems but are increasingly degraded by human impacts. Protected areas have been shown to conserve species diversity, but their effectiveness at maintaining functional diversity over time is less well known, despite the fact that functional diversity likely reveals more ecological information than taxonomic diversity. By extension, the degree to which species loss decreases functional diversity within protected areas is also unknown; functional redundancy may buffer communities from loss of functional diversity from some local extinctions. Using eight years of camera trap data, we quantified annual functional dispersion of the large mammal community in the Volcán Barva region of Costa Rica and tested for changes in functional dispersion over time in response to environmental and anthropogenic predictors. We quantified functional redundancy based on simulated declines in functional dispersion with species loss. Observed functional dispersion did not change significantly over time and was not associated with measured environmental or anthropogenic predictors. Quantitative modeling of observed functional traits over time did not identify significant changes. We did however find qualitative trends in relative trait proportions, which could be indicative of functional change in the future. We found high functional redundancy, with average simulated functional dispersion declining significantly only after 9 out of 21 large mammal species were lost from the community. We cautiously suggest that protected tropical rain forests can conserve functional diversity over the course of a decade even in heavily fragmented landscapes. Abstract in Spanish is available with online material. RESUMEN: A nivel mundial, las selvas tropicales representan algunos de los ecosistemas más diversos y funcionalmente ricos, pero se ven cada vez más degradados por los impactos humanos. Se ha demostrado que las áreas protegidas conservan la diversidad de especies, pero su efectividad para mantener la diversidad funcional a largo plazo es menos clara, a pesar de que la diversidad funcional probablemente revela más información ecológica que la diversidad taxonómica. Por extensión, también se desconoce el grado en que la pérdida de especies disminuye la diversidad funcional dentro de las áreas protegidas; La redundancia funcional puede proteger a las comunidades de la pérdida de diversidad funcional de algunas extinciones locales. Utilizando ocho años de datos de trampa de cámara, cuantificamos la dispersión funcional anual de la comunidad de mamíferos grandes en la región del Volcán Barva de Costa Rica y probamos los cambios en la dispersión funcional a largo plazo en respuesta a predictores ambientales y antropogénicos. Cuantificamos la redundancia funcional basada en disminuciones modeladas en la dispersión funcional con pérdida de especies. La dispersión funcional no cambió significativamente con el tiempo y no se asoció con los predictores ambientales o antropogénicos medidos. El modelado cuantitativo del cambio en los rasgos funcionales a largo plazo no identificó cambios significativos. Sin embargo, encontramos tendencias cualitativas en las proporciones relativas de los rasgos, que podrían ser indicativos de un cambio funcional en el futuro. Encontramos una alta redundancia funcional, con una dispersión funcional promedio que disminuyó significativamente solo después de que 9 de 21 especies de mamíferos grandes se perdieron de la comunidad. Sugerimos con cautela que las selvas tropicales protegidas pueden conservar la diversidad funcional en el transcurso de una década, incluso en paisajes muy fragmentados.